The reliance of the media elite on citizen journalism during news coverage - goumichi, imane; bouaziz, boubaker (Journal of Social Sciences and Humanities, 2025)
This study aims to explore the reasons behind the Algerian media elite's reliance on citizen journalism as a source of news. The participation of citizen journalists in news coverage, content production, and visual reporting has been a central topic in numerous academic studies and scientific discussions among specialists in the field of new media and communication sciences. This interest has grown significantly with the rapid advancement and widespread adoption of new technologies, including smart devices, digital platforms, and interactive social networks, which have become integral to various aspects of life, including media activities. This evolution has captured the attention of media organizations, particularly news television channels, leading them to engage with and utilize such content. Consequently, citizen journalism has emerged as an active contributor to achieving the principles of public service media.